2019
DOI: 10.3389/fncel.2019.00325
|View full text |Cite
|
Sign up to set email alerts
|

Systemic L-Buthionine -S-R-Sulfoximine Treatment Increases Plasma NGF and Upregulates L-cys/L-cys2 Transporter and γ-Glutamylcysteine Ligase mRNAs Through the NGF/TrkA/Akt/Nrf2 Pathway in the Striatum

Abstract: Glutathione (GSH) is the most abundant intracellular antioxidant. GSH depletion leads to oxidative stress and neuronal damage in the central nervous system (CNS). In mice, the acute systemic inhibition of GSH synthesis by L-buthionine-S-R-sulfoximine (BSO) triggers a protective response and a subsequent increase in the CNS GSH content. This response might be modulated by a peripheral increment of circulating nerve growth factor (NGF). NGF is an important activator of antioxidant pathways mediated by tropomyosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…3A ). BSO is an inhibitor of GSH ( 39 ). In vitro , NAC significantly reduced MG-induced ROS elevation compared with that in the MG group.…”
Section: Resultsmentioning
confidence: 99%
“…3A ). BSO is an inhibitor of GSH ( 39 ). In vitro , NAC significantly reduced MG-induced ROS elevation compared with that in the MG group.…”
Section: Resultsmentioning
confidence: 99%
“…Valdovinos-Flores and Gonsebatt (2013) observed significant transcription of ngfb at 2 h after a 14-mg/kg iAs i.p. injection, which was associated with the activation of the TrkA/Akt/NFκB signaling pathway in the liver but not in the striatum of mice (Valdovinos-Flores et al, 2019). However, systemic activation of this pathway could induce GSH synthesis in other brain regions such as the cortex and cerebellum at 24 h and 9 days ( Figures 1C,D).…”
Section: Discussionmentioning
confidence: 96%
“…The in vivo experiments of the present study demonstrated that NGF was able to inhibit the conversion of MSCs to the proinflammatory type in diabetes and further decreased the infiltration of T cells and macrophages in periodontal tissues. TrkA is the major high-affinity receptor of NGF and has an irreplaceable role in the growth and development of the nervous system and the maintenance of neuronal characteristics (29). The combination of NGF and TrkA may further activate the MAPK signaling pathway and promote stem cell proliferation and differentiation (30,31).…”
Section: Discussionmentioning
confidence: 99%